2021
DOI: 10.1016/j.csbj.2021.01.019
|View full text |Cite
|
Sign up to set email alerts
|

An extracellular lipase from Amycolatopsis mediterannei is a cutinase with plastic degrading activity

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…The AmCut gene was known from previous studies (Tan et al 2021 ). It was a 930 bp gene with GenBank ID of ADJ49206.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The AmCut gene was known from previous studies (Tan et al 2021 ). It was a 930 bp gene with GenBank ID of ADJ49206.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies in this laboratory had cloned a truncated AmCut gene lacking the N-terminal signal peptide and showed that the enzyme was expressed as a soluble protein in E. coli cytosol (Tan et al 2021 ). To further examine the role of the signal peptide on AmCut activity, the entire AmCut gene, including the putative signal peptide, was cloned (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations